2002
DOI: 10.1074/jbc.m108917200
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation of Cytochrome P450cam with Putidaredoxin

Abstract: We have performed resonance Raman studies on ferrous NO-and CO-adducts of cytochrome P450 cam and investigated the effects of diprotein complex formation with reduced putidaredoxin. We have found that the Fe-NO stretching mode of NO-P450 cam can be resolved into two peaks at 551 and 561 cm ؊1 , and the binding of putidaredoxin increases the intensity of the high frequency component. Because the Fe-NO mode has been shown to be more sensitive to the nature of the heme proximal ligand than to the distal pocket en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…The enhanced electron donation was confirmed by a slight lowering of 36 mV in the mutant compared with that of WT enzyme (18,27). Vibrational spectroscopic studies on the CO, NO, and oxy complexes have shown that Pdx binding enhances electron donation from the axial Cys, thereby promoting O-O bond cleavage (11)(12)(13)15).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The enhanced electron donation was confirmed by a slight lowering of 36 mV in the mutant compared with that of WT enzyme (18,27). Vibrational spectroscopic studies on the CO, NO, and oxy complexes have shown that Pdx binding enhances electron donation from the axial Cys, thereby promoting O-O bond cleavage (11)(12)(13)15).…”
Section: Resultsmentioning
confidence: 78%
“…Electrons are provided by an iron-sulfur protein, putidaredoxin (Pdx). In the electron transfer steps, P450cam forms a complex with reduced Pdx, and the P450cam active site is perturbed as indicated by various spectroscopic studies including NMR (7,8), EPR (9,10), resonance Raman (11)(12)(13), and infrared (14,15). Because nonphysiological redox proteins such as ferredoxin and adrenodoxin cannot support the monooxygenation reaction or induce the conformational changes (7,16), the Pdxinduced changes in P450cam are thought to be important for the "effector" function of Pdx in addition to its reductase activity.…”
mentioning
confidence: 99%
“…The tilt of the heme plane upon the binding of Pdx is supported by the shifts of the low frequency Raman lines in the 300 -800 cm Ϫ1 region (23). Although the specific assignments have not yet been reported for P450cam, the low frequency Raman lines would involve the vibrational modes of the peripheral groups of the heme as observed for myoglobin (55).…”
Section: Nmr Spectra In the Presencementioning
confidence: 70%
“…Other important feature of the P450cam⅐Pdx complex is that Pdx induces conformational changes of P450cam upon the complex formation (21)(22)(23)(24)(25)(26)(27)(28). EPR and resonance Raman studies clearly exhibited that the complex formation with Pdx converts the spin-state of ferric P450cam from the high to low spin state (21,24).…”
mentioning
confidence: 99%
“…In resonance Raman (17, 18), IR (19), NMR (20,21), and EPR studies (11,22), Pdx binding has been shown to cause protein conformational changes that distort the P450-CAM heme structure and, especially, the Fe-S bond. In particular, Tosha et al (20) proposed that Pdx binding leads to structural changes that facilitate oxygen activation, and Unno et al (18) suggested that the structural changes may correlate with H-bonding to the proximal Cys. Similarly, Nagano et al (19) proposed that Pdx binding promotes electron donation from the proximal Cys to the iron-bound O 2 to facilitate O-O bond cleavage.…”
mentioning
confidence: 99%